Breast PET/MRI Hybrid Imaging and Targeted Tracers. Issue 2 (27th September 2022) - Romeo, Valeria; Helbich, Thomas H.; Pinker, Katja
Abstract : The recent introduction of hybrid positron emission tomography/magnetic resonance imaging (PET/MRI) as a promising imaging modality for breast cancer assessment has prompted fervent research activity on its clinical applications. The current knowledge regarding the possible clinical applications of hybrid PET/MRI is constantly evolving, thanks to the development and clinical availability of hybrid scanners, the development of new PET tracers and the rise of artificial intelligence (AI) techniques. In this state‐of‐the‐art review on the use of hybrid breast PET/MRI, the most promising advanced MRI techniques (diffusion‐weighted imaging, dynamic contrast‐enhanced MRI, magnetic resonance spectroscopy, and chemical exchange saturation transfer) are discussed. Current and experimental PET tracers ( 18 F‐FDG, 18 F‐NaF, choline, 18 F‐FES, 18 F‐FES, 89 Zr‐trastuzumab, choline derivatives, 18 F‐FLT, and 68 Ga‐FAPI‐46) are described in order to provide an overview on their molecular mechanisms of action and corresponding clinical applications. New perspectives represented by the use of radiomics and AI techniques are discussed. Furthermore, the current strengths and limitations of hybrid PET/MRI in the real world are highlighted. Evidence Level: 2 Technical Efficacy: Stage 2